2020
DOI: 10.1007/s00268-020-05603-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Needs of Internally Displaced Persons in Kerenik, West Darfur, Sudan

Abstract: Background The burden of surgical disease in refugee and internally displaced person (IDP) populations has not been well defined. Populations fleeing conflict are mobile, limiting the effectiveness of traditional sampling methods. We employed novel sampling and survey techniques to conduct a population-based surgical needs assessment amongst IDPs in Kerenik, West Darfur, Sudan, over 4 weeks in 2008. Methods Satellite imagery was used to identify man-made structures. Ground teams were guided by GPS to randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…al have reported on surgical need among forced migrant populations in Sudan and Lebanon, respectively, our study adds to this nascent body of literature by performing, to the best of our knowledge, the first and largest study of prevalence of surgical disease in a refugee population in sub‐Saharan Africa using cluster random design sampling and population‐based, household survey methods. [12, 13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al have reported on surgical need among forced migrant populations in Sudan and Lebanon, respectively, our study adds to this nascent body of literature by performing, to the best of our knowledge, the first and largest study of prevalence of surgical disease in a refugee population in sub‐Saharan Africa using cluster random design sampling and population‐based, household survey methods. [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the alarming and growing number of refugees globally, little empirical attention has been paid to forced migrant populations. To our knowledge, only few studies have attempted to characterize the burden of surgical disease in forced migrant populations, and no household‐based study has been done in sub‐Saharan Africa to estimate the prevalence of surgical disease among refugees [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Several studies have underscored the unmet obstetric surgical needs among forcibly displaced individuals. 10,19 Estimates indicate approximately 196,000 emergency obstetric procedures were potentially required for forcibly displaced women of reproductive age. 20 Similarly, obstetric complications, such as caesarean deliveries for maternal indications, postpartum haemorrhage and ectopic pregnancies, accounted for approximately 10% of the total minimum surgical need among this population, all of which remained unaddressed (Figure 2).…”
Section: Obstetric Complicationsmentioning
confidence: 99%
“…Refugees are disproportionately affected by trauma-related injuries, resulting in substantial unmet surgical needs. 8,19,21 This vulnerable population often faces an elevated risk of sustaining severe injuries, including gunshot wounds, shrapnel injuries, burns, fractures, amputations and soft tissue injuries (Figure 2). 19 Recent studies have demonstrated the extent of unmet surgical needs among trauma patients in refugee populations.…”
Section: Trauma-caused Morbidity and Mortalitymentioning
confidence: 99%
“…However, the war peaked in 2004, which has ended over 300,000 lives, left around 3 million Internally Displaced Persons (IDPs) from their homes, and suffered from poor health care services. 23 Moreover, their limiting access to health services may prevent them from diagnostics and medical management in the event of an outbreak and make them at the highest risk of COVID-19 infection. To date, however, little is known about COVID-19 myths among the IDPs in Sudan.…”
Section: Introductionmentioning
confidence: 99%